A compact UWB MIMO antenna with neutralization line for WLAN/ISM/mobile applications. Issue 11 (31st July 2019) - Tiwari, Rakesh N.; Singh, Prabhakar; Kanaujia, Binod K.
Abstract: A novel design of 2 × 2 multiple‐input‐multiple‐output (MIMO) antenna is reported for ultra‐wideband applications. The neutralization line is implemented to minimize the mutual coupling between the radiating patches. The overall dimension of the designed antenna is 21 × 34 × 1.6 mm 3 . This antenna covers the measured bandwidth of 95.0% (3.52‐9.89 GHz) with better isolation (≤−22 dB) over the entire operating frequency band. The measured gain varies from 3.08 to 5.12 dBi over the entire band. The various antenna parameters such as S ‐parameters, gain, efficiency, envelope correlation coefficient, mean effective gain, channel capacity loss, total active reflection coefficient, and radiation patterns are calculated and corresponding results are validated with the measured results.